ANALISIS PRESTASI KERJA GURU DI MADRASAH IBTIDAIYAH SE-KOTA PEKANBARU - Erza Intan Anggraini; Almasdi Syahza; Murni Baheram (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2018)
This research aimed to analyze teachers’ work achievement at Islamic PrimarySchools within the Municipality of Pekanbaru. To achieve this aim, an information analysis wasrequired among others: (1) knowing the teachers’ work achievement in terms of pedagogicalcompetence aspects (2) knowing the teachers’ work achievement through personalitycompetence aspects, (3) knowing the teachers’ work achievement through social competenceaspects, and (4) knowing the teachers’ work achievement through professional competenceaspects.The sample of the research was teachers of Islamic Primary School teachers withinPekanbaru Municipality totalling 150 teachers. The data were gathered from the sample usingRandom Sampling technique. The analyzed data came from the respective variables throughthe documentation of Teachers Work Performance (PKG) at Islamic Primary Schools withinPekanbaru Municipality.The findings of the research showed that the teachers’ workperformances at Islamic Primary Schools in Pekanbaru Municipality on pedagogical competence,personality competence, social competence and professional competence were in very goodcategory. The highest competence was contributed by pedagogical competence reaching 51,84 %, while the lowest competence was personality competence which was 20,07 %. Theseresults indicated that teachers at Islamic Primary Schools in Pekanbaru could manage learningbeginning from the planning of learning to the maximum implementation of teaching and learning.